Theorizing the advent of weaponized drones as techniques of domestic paramilitary policing. (August 2019) - Davis, Oliver
The killing of Micah Johnson by Dallas police using a teleguided exploding robot on 8 July 2016 is the first known example of the use of a killer drone by US law enforcement in the domestic arena. This repatriation of the drone, under conditions of racialized urban unrest designated as exceptional, was predicted by Didier Bigo and follows a familiar pattern whereby coercive security technologies are tested abroad before finding their way 'home' to arm police forces that are becoming increasingly paramilitary in style and conduct. I use the Dallas incident to probe the cogency and limits of 'drone theory' and to consider its application in domestic policing contexts. I work through three broadly delineated areas of scepticism about drone theory as it intersects with policing and, in so doing, develop my own account of the weaponized policing drone as a defining techno-cultural element within the emergent form of neoliberal political rationality I call 'governance'.